2021
DOI: 10.1101/2021.08.26.456137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Large-Scale Investigation of White Matter Microstructural Associations with Reading Ability

Abstract: Reading involves the functioning of a widely distributed brain network, and white matter tracts are responsible for sending information between constituent network nodes. Several studies have analyzed fiber bundle microstructural properties to shed insights into the neural basis of reading abilities and disabilities. Findings have been inconsistent, potentially due to small sample sizes and varying methodology. To address this, we analyzed a large data set of 690 children ages 5-18 using state-of-the-art neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 147 publications
(179 reference statements)
1
3
0
Order By: Relevance
“…These results are also generally in line with those reported by Meisler and Gabrieli(36) which did not find any significant relationship between FA and reading skills in a subset of the HBN dataset. Though the authors observed a relationship between FA and phonemic decoding in the right SLF and the left ICP in participants above age 9, their analysis focused on a different measure of reading skill (TOWRE) and relied on a different analytic pipeline (TractSeg(65)), which may explain the subtle differences between their findings and the present results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are also generally in line with those reported by Meisler and Gabrieli(36) which did not find any significant relationship between FA and reading skills in a subset of the HBN dataset. Though the authors observed a relationship between FA and phonemic decoding in the right SLF and the left ICP in participants above age 9, their analysis focused on a different measure of reading skill (TOWRE) and relied on a different analytic pipeline (TractSeg(65)), which may explain the subtle differences between their findings and the present results.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a recent cross-sectional analysis of the Healthy Brain Network (HBN) dataset (32), representing the largest study of white matter and reading to date, did not reveal any significant differences in FA between struggling and typical readers nor a significant relationship between FA and reading scores (35). These findings not only raise questions about the observed relationships between reading and the white matter in smaller, cross-sectional studies, but also about the impact of sample makeup on these brain-behavior correlations, as the HBN dataset is a much more diverse sample than those found in traditional single-lab studies.…”
Section: Introductionmentioning
confidence: 99%
“…As regards dyslexia, this disorder of reading is closely linked to linguistic cognition in many affected individuals, including reduced phonological awareness and sometimes language impairment (54)(55)(56). Dyslexia has also been linked to altered frontal-temporal structural connectivity via the arcuate fasciculus, although results on this have been inconsistent across studies (57,58). While reading is a cultural innovation, it recruits much of the neural circuitry that underpins the human capacity for oral language (59).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is unknown if lack of visual experience may lead to the preservation of connections between VTC and somatosensory cortex, which in turn, may enable VTC to respond to haptic inputs in individuals who are congenitally blind 100 . Critically, our framework enables measuring the fine-grained white matter connections of VTC in individual infants longitudinally 101 , increasing accuracy and precision in measuring the interplay between white matter connections, functional regions, and anatomy across development. Our framework opens new opportunities not only for evaluating development of white matter associated with functional regions in large infant datasets [74][75][76][77][78] but also for early identification and assessment of developmental disorders associated with VTC such as autism [102][103][104][105] , Williams syndrome 106 , congenital prosopagnosia 107,108 , and dyslexia 109,[102][103][104][105] .…”
Section: Implications For Theories Of Functional Development Of Vtcmentioning
confidence: 99%